IPad for seniors for dummies - Muir, Nancy 1954- (Wiley, 2010)
Your iPad is an e-book reader, music player, movie screen, online shopping center, mailbox, and more-- all in a device small enough to take anywhere. Learn how to set it up and use its features, including great options that make life a lot easier if you have vision or hearing challenges.
Print version record
Keywords: iPad (Computer); Tablet computers; Computers and older people; iPad (Ordinateur); Tablettes électroniques; Ordinateurs et personnes âgées; COMPUTERS; Hardware; Personal Computers; General; COMPUTERS; Hardware; Handheld Devices; COMPUTERS; Microprocessors; Portable computers